Review paperThe preventive role of coenzyme Q10 and other antioxidants in injuries caused by oxidative stress - Feher, Janos; Nemeth, Eszter; Nagy, Viktor; Lengyel, Gabriella; Feher, Janos (Archives of Medical Science, 2007)
Oxidative stress contributes to the generation of many different pathological conditions. Its key feature is an imbalance between free radical formation and their elimination processes. In this mini-review the authors give an introduction to the basic mechanisms of free radical formation, their physiological and pathological roles and the possible defective mechanisms involved in the maintenance of the living organism’s balanced oxidative state. Antioxidants are very important in the battle against harmful oxidative stress. Therefore they can be used to prevent several diseases and even to cure them. In this short overview the authors discuss the role of some antioxidants such as coenzyme Q10 (ubidecarenone), lipoic acid, selenium, omega-3 fatty acids and vitamin E, emphasizing their increased effectiveness with their combined applications.